Since \( y \) varies directly as the square root of \( x \), we can express this relationship with the equation:
\[ y = k \sqrt{x} \]
where \( k \) is a constant.
Given that \( y = 27 \) when \( x = 9 \), we can substitute these values into the equation to find \( k \):
\[ 27 = k \sqrt{9} \]
Calculating \( \sqrt{9} \), we find:
\[ \sqrt{9} = 3 \]
So we can rewrite the equation:
\[ 27 = k \cdot 3 \]
Now, solve for \( k \):
\[ k = \frac{27}{3} = 9 \]
Now that we have found \( k \), our equation relating \( y \) and \( x \) is:
\[ y = 9 \sqrt{x} \]
Next, we want to find \( x \) when \( y = 63 \). We substitute 63 for \( y \) in the equation:
\[ 63 = 9 \sqrt{x} \]
To isolate \( \sqrt{x} \), divide both sides by 9:
\[ \sqrt{x} = \frac{63}{9} = 7 \]
Now, square both sides to solve for \( x \):
\[ x = 7^2 = 49 \]
Thus, when \( y = 63 \), \( x \) equals:
\[ \boxed{49} \]